Profil Fisiko-Kimia Minyak Kulit Batang Pulosari (Alyxia reinwardtii Bl.) dan Aktivitas Antioksidannya - Franciska Alvina; Hartati Soetjipto; Sri Hartini (LPPM, Institut Teknologi Sepuluh Nopember, 2023)
Pulosari bark is one part of the plant that has medicinal properties and a distinctive aroma, it is widely used in various herbal recipes in Indonesia. The purpose of this study was to determine the yield, Physico-chemical properties, and antioxidant power of Pulosari bark oil. Based on the research that has been done, the yield of Pulosari bark oil by maceration method using n-hexane produces an average oil of 2.658 ± 0.098%. The Physico-chemical properties of the oil include density, acid number, peroxide number, and saponification number respectively are 0.98±0 g/mL; 92.875±4.954 Mek O2/kg; 11.214±0.776 mg KOH/g; and 105.678±12.921 mg KOH/g. The most dominant composition of Pulosari stem bark oil compounds are Cyclopentadecanone, 2-hydroxy- (25.97%); Hexadecanoic acid (14.47%); Ethyl linoleate (9.70%); 2H-1-Benzopyran-2-one (9.52%); and 1,2-Benzenedicarboxylic acid, mono(2-Ethylhexyl) ester (8.34%). The antioxidant activity of the oil tested with DPPH resulted in an IC50 value of 296,700 g/mL and was categorized as very weak.